REVITALISASI TATA LAMBANG KOMUNIKASI TRADISIONAL WAYANG INDONESIA SEBAGAI MILIK DONIA - Kertopati, Ton (Universitas Prof. Dr. Moestopo (Beragama), 2010)
We now come to the consideration of convergence, an issue that seems to be particularly vecing to social scientists especially cultural. Â Much of the difficulty of dealing with this problem stem from the failure to distinguish with sufficient precision the different elements of a very complex situation. Â A minimum list of such elements should include the following: a.Structures of patterns of social relationship. b.System of popular attitudes, value and behavior. c. System ofpolitical and economic control.